Content and affect in persecutory delusions - Green, C; Garety, P; Freeman, D; Fowler, D; Bebbington, P; Dunn, G; Kuipers, E (2006)
Objectives. The study aimed to explore the content of persecutory delusions and its potential links with levels of affective disturbance. Detailed examinations of the phenomenology of delusional beliefs have been rare, but are important for furthering theoretical and clinical understanding. Design. A cross-sectional investigation of 70 individuals with current persecutory delusions was conducted. Methods. Taped semi-structured clinical interviews were transcribed for each participant. Using a coding frame devised for the current study, a detailed description of persecutory content was made. Scores on the Beck Depression and Anxiety Inventories, the Rosenberg Self-esteem Scale and the Psychotic Symptom Rating Scales were used as indicators of emotional distress. Results. Data were gathered on the identity and type of persecutor, pervasiveness of threat and the power of the persecutor. Reliability was good. Beliefs involving multiple persecutors, human in nature and identifiable to the individual were common. For the majority threat was severe, ongoing and enduring and coupled with frequent feelings of vulnerability. Specific aspects of delusional content were found to be associated with emotional distress. For example, if participants felt more power in the face of persecution this was coupled with lower depression and higher self-esteem. Conclusions. Persecutory delusions are beliefs concerning severe threat, particularly of physical harm including death, which is personally significant, frequently involving multiple persecutors known to the individual. Depression is higher in those who felt less powerful than their persecutors. Associations, such as this, with emotional distress support a direct role for emotion in delusion formation and maintenance. It is consistent with cognitive models of delusions which emphasize the importance of considering emotional distress in the context of belief appraisal, although interpretation of the results is limited by the cross-sectional study design. Recognizing these links may in turn aid therapists in identifying aspects of beliefs that might be targeted to facilitate emotional change. © 2006 The British Psychological Society.